Land and Livelihood Issues in Different Stages of Tribal Resettlement - Chaturvedi, Arun; Patil, Nitin; Hajare, Trilok (Indian Forester, 2012)
A comparative study on livelihood of undisturbed forest village and relocated village is presented. Analysis revealed that agriculture as a sole occupation could not provide livelihood to the tribal. The relocated village (Tetu in Amravati district) was settled on agriculturally poor soils. Denial of access for NTFP collection and poor agricultural productivity were the main factors that led to impoverishment of villagers. Similarly, villages in Gondia district situated in similar domain/settings had relatively better soils, but could not support the population adequately. However, permission to collect NTFP made the difference. It was also observed that apart from modernising agriculture, it is essential to impart skills to the villagers to derive income from sources other than agriculture (e.g. pisciculture, poultry) before displacing them. It was also apparent that the relocation on fringes of forest with poor soils could force tribal to utilize forest resources without heed to conservation. The policy for relocation thus needs to be formulated based on the findings.